2013
DOI: 10.1186/1465-9921-14-119
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine exposure during differentiation causes inhibition of N-myc expression

Abstract: BackgroundThe ability of chemicals to disrupt neonatal development can be studied using embryonic stem cells (ESC). One such chemical is nicotine. Prenatal nicotine exposure is known to affect postnatal lung function, although the mechanisms by which it has this effect are not clear. Since fibroblasts are a critical component of the developing lung, providing structure and secreting paracrine factors that are essential to epithelialization, this study focuses on the differentiation of ESC into fibroblasts usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…Our results suggest that smoke extracts might be inhibiting the cytoplasmic exchange of survival and differentiation signals, by down-regulating Cx43 expression in MSCs. In addition to the fact that nicotine might be a player in the impairment of differentiation 69 , smoke contains other ingredients that are toxic and could impair differentiation as well 70 , 71 . Subsequently, tissue repair might be compromised upon exposure to both cigarette and e-cigarette.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that smoke extracts might be inhibiting the cytoplasmic exchange of survival and differentiation signals, by down-regulating Cx43 expression in MSCs. In addition to the fact that nicotine might be a player in the impairment of differentiation 69 , smoke contains other ingredients that are toxic and could impair differentiation as well 70 , 71 . Subsequently, tissue repair might be compromised upon exposure to both cigarette and e-cigarette.…”
Section: Discussionmentioning
confidence: 99%
“…3,28 In animal models, tobacco smoke and nicotine exposure during in utero or early postnatal life has been shown to alter expression of genes involved in cell proliferation, T-helper (Th) type 1 (Th1) and type 2 (Th2) immune balance, fibrosis, and viral immune responses (Table 1). [29][30][31][32][33] Nicotine Exposure and Lung Development Nicotinic acetylcholine receptors (nAChRs) are ligandgated ion channels that enable flow of cations through the channel when bound by acetylcholine and other nAChR agonists, including nicotine. These receptors consist of five transmembrane subunits that form a central ion pore.…”
Section: Normal Lung Developmentmentioning
confidence: 99%
“…36,37 The effects of nicotine may occur very early in lung development. For example, Ben-Yehudah and colleagues 29 have shown that nonhuman primate embryonic stem cells express nAChRs. In their study, exposure of nicotine caused downregulation of n-Myc expression and differentiation of nonhuman primate embryonic stem cells into fibroblasts, demonstrating that exposure to nicotine during embryogenesis can affect embryonic stem cell differentiation.…”
Section: Normal Lung Developmentmentioning
confidence: 99%
“…There is strong evidence from animal studies on the adverse impact of antenatal smoke exposure on lung development (10,11). The effects of nicotine may occur very early, affecting embryonic stem cell differentiation (66). Intrauterine smoke exposure disrupts lung development in mice, resulting in a pathological picture similar to BPD (67).…”
Section: Discussionmentioning
confidence: 99%